A COMPARATIVE ANALYSIS OF INTERNET FINANCIAL REPORTING INDEX OF SHARIA COMMERCIAL BANKS IN INDONESIA, MALAYSIA, IRAN, AND SUDAN - Hayati, Putri; Suprayogi, Noven (Universitas Airlangga, 2018)
The purpose of this study was to determine the differences of Internet Financial Reporting Quality. This study was using quantitative approach with one way anova and kruskal wallis. The population of this study was official website of islamic banks in Indonesia, Malaysia, Iran, Sudan. The data was collected from official website sentral bank in each country and official website of islmaic bank in each country. Data that being used was primary data. The result of this study showes that there was significant differences of Internet Financial Reporting Quality between Indonesia, Malaysia, Iran, Sudan. The difference is caused there are significant differences between the quality of content, timeliness, user support components. Meanwhile, there is no differences between technology components.Keywords: Internet Financial Reporting, Indonesia, Malaysia, Iran, Sudan